2010
DOI: 10.1016/j.yjmcc.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mitochondrial function as a harbinger of cardiomyopathy: Lessons from the dystrophic heart

Abstract: While compelling evidence supports the central role of mitochondrial dysfunction in the pathogenesis of heart failure, there is comparatively less information available on mitochondrial alterations that occur prior to failure. Building on our recent work with the dystrophin-deficient mdx mouse heart, this review focuses on how early changes in mitochondrial functional phenotype occur prior to overt cardiomyopathy and may be a determinant for the development of adverse cardiac remodelling leading to failure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 171 publications
(201 reference statements)
4
44
1
Order By: Relevance
“…Interestingly, in the latter study, skeletal muscles, which already present a severe pathological phenotype at this age, displayed overt mitochondrial respiratory defects, suggesting that respiratory dysfunctions are detectable only when myopathy is well established. Our data thus indicate that before cardiomyopathy, an experimental stress is required to unmask abnormal mitochondrial responses in mdx hearts, as observed in other models of acquired cardiomyopathy (9).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, in the latter study, skeletal muscles, which already present a severe pathological phenotype at this age, displayed overt mitochondrial respiratory defects, suggesting that respiratory dysfunctions are detectable only when myopathy is well established. Our data thus indicate that before cardiomyopathy, an experimental stress is required to unmask abnormal mitochondrial responses in mdx hearts, as observed in other models of acquired cardiomyopathy (9).…”
Section: Discussionsupporting
confidence: 66%
“…As we suggested recently (9), the prevention of the PTP opening could constitute a mechanism by which sildenafil protects the dystrophin-deficient heart against cardiomyocyte damage in response to stress. In fact, the activation of cGMP signaling by sildenafil could potentially inhibit the PTP opening indirectly through the modulation of key cellular regulators of the PTP, such as intracellular Ca 2Ď© levels and oxidative stress (58), which are increased in DMD (53).…”
mentioning
confidence: 74%
“…Superoxide anion generated by NAD(P)H-oxidase has an important role in the pathogenesis of cardiovascular diseases and scavenging superoxide anion can be considered as a reasonable therapeutic strategy [199,200]. In this review we demonstrate that scavenging superoxide anion by tempol or EUK-8 or administration of PEG-superoxide dismutase inhibits collagen production in cardiac fibroblasts.…”
Section: Perspectivesmentioning
confidence: 84%
“…However, others have not observed this effect in cardiomyocytes isolated from mice (22). Even though it is unclear which cell type is targeted by sildenafil, total heart extracts from patients with end-stage congestive heart failure have increased PDE5 expression via a mechanism involving oxidative stress (23), and a recent study has shown an increase in oxidative stress in the hearts of young mdx mice (24). Whether this increase in PDE5 expression takes place in cardiomyocytes, myofibroblasts, or vascular smooth muscle cells is still to be determined.…”
Section: Discussionmentioning
confidence: 99%